Synthesis, Spectral, Thermal and Biological Studies of 4-Cyclohexyl-3-(4-nitrophenyl)methyl-1,2,4-triazolin-5-thione and Its Copper(II) Coordination Compound, [CuCl(2)(H(2)O)(2)L(2)] - Czylkowska, Agnieszka (Materials (Basel), 2020)
One of the strategies for seeking new biologically active substances is to modify compounds with potential biological activity. In this paper, 1,2,4-triazolin-5-thione derivative (3) was obtained in the cyclization reaction of appropriate thiosemicarbazide (2) as an organic ligand. The copper(II) complex, [CuCl(2)(H(2)O)(2)L(2)] (L=4-cyclohexyl-3-(nitrophenyl)methyl-1,2,4-triazolin-5-thione) (Cu-3) was prepared in a reaction of free ligand (3) with a CuCl(2)·2H(2)O solution in MeOH/EtOH mixture at room temperature. TGA data show that Cu-3 and free ligand are stable at room temperature. Both compounds were screened in vitro for antibacterial and antifungal activities using the broth microdilution method. The obtained complex (Cu-3) showed higher antibacterial effect, especially towards Gram-positive bacteria (with moderate activity and Minimal Inhibitory Concentration MIC = 250–500 µg/mL) than the free ligand (3) (with mild or no bioactivity and MIC ≥ 1000 µg/mL). In turn, yeasts, belonging to Candida albicans, exhibited similar sensitivity to both the copper(II) complex (Cu-3) and the organic ligand (3). The anticandidal activity of these compounds was moderate (MIC = 500 µg/mL), or, in the case of other Candida spp., lower (MIC ≥ 1000 µg/mL).